Novel Ultrasonographic Fatty Liver Indicator Can Predict Hepatitis in Children With Non-alcoholic Fatty Liver Disease - Liu, Hsien-Kuan; Yang, Ming-Chun; Su, Yu-Tsun; Tai, Chi-Ming; Wei, Yu-Feng; Lin, I-Chun; Tsai, Ching-Chung (Frontiers in Pediatrics, 2019)
Background: Childhood non-alcoholic fatty liver disease (NAFLD) is a public health issue worldwide. To date, liver biopsy remains the gold standard for diagnosing the severity of NAFLD. However, this invasive procedure might contribute to complications. Owing to this reason, a good non-invasive tool to estimate NAFLD in children is urgently needed. We sought to investigate whether a non-invasive semi-quantitative ultrasonographic fatty liver indicator (US-FLI) can estimate NAFLD in children. Methods: Children aged between 10 and 18 years were enrolled prospectively. Abdominal ultrasonography was performed by a single experienced pediatric gastroenterologist and the non-invasive semi-quantitative US-FLI score were used. Patients were diagnosed with NAFLD if they had a US-FLI score ≥ 2. The anthropometric measures, obesity-related biochemical results, and levels of tumor necrosis factor-α, interleukin-6, caspase-cleaved cytokeratin fragment of cytokeratin 18 (M30), and adiponectin were also checked. Results: Overall, 117 children aged 10 to 18 years were enrolled. The anthropometric measures and obesity-related biochemical parameters (hsCRP, triglyceride, uric acid, AST, ALT, γ-GT, homeostatic model assessment insulin resistance (HOMA-IR), and M30) were significantly higher in the obesity group than in the non-obesity group (p < 0.05). Similarly, the US-FLI score was significantly higher in the obesity group than that in the non-obesity group (p < 0.001). Multiple linear regression showed that the US-FLI score was significantly associated with the waist-to-height ratio, uric acid, adiponectin, and M30 levels (all p < 0.05) in children with obesity. The US-FLI score ≥ 6 was the optimal cut-off point for predicting the hepatitis in children with NAFLD. The area under the receiver operating characteristic curve was 0.710 (95% CI: 0.572–0.847; p = 0.005). Conclusions: The non-invasive US-FLI score can predict hepatitis in children with NAFLD without mandatory liver biopsy. Moreover, the waist-to-height ratio, uric acid, adiponectin, and M30 levels were significantly associated with US-FLI score in children with obesity.